The Influence Of Internal Control System Of Accounts Receivables On Bad Debts - Fina, Yurnida; Susilawati , Made; Ndun, Ariyon Stefen (GOVERNORS, 2025)
This study aims to examine the influence of the accounts receivable internal control system on bad debts at the Swasti Sari Savings and Loan Cooperative in Kupang during the period of observation. The research employs a quantitative descriptive approach with simple linear regression analysis. Both primary and secondary data are utilized, collected through interviews, questionnaires, and documentation. The research variables consist of the accounts receivable internal control system as the independent variable and bad debts as the dependent variable. The findings indicate that although the internal control system of accounts receivable contributes to the management of bad debts, its influence is not statistically significant. This suggests that bad debts are also affected by other factors beyond the internal control system examined in this study. Therefore, it is recommended that the cooperative continue to improve the effectiveness of its accounts receivable internal control system while considering additional factors that may influence bad debts. Future studies are encouraged to incorporate other relevant variables to obtain a more comprehensive understanding of the determinants of bad debts.